Causes of nonlinearity of the oxygen uptake efficiency slope: a prospective study in patients with chronic heart failure. (29th August 2020) - Niemeijer, Victor M; van 't Veer, Marcel; Schep, Goof; Spee, Ruud F; Hoogeveen, Adwin; Kemps, Hareld MC
Abstract: Background: The oxygen uptake efficiency slope (OUES) is an exercise parameter with strong prognostic value in the heart failure population. Yet, the optimal determination method of OUES remains unclear. The purpose of the present study was to investigate the influence of the ventilatory anaerobic threshold (VAT) and occurrence of a plateau in oxygen uptake (VO2 ) on determination of OUES from submaximal exercise data in patients with chronic heart failure (CHF). Methods and Results: Ninety-eight CHF patients (New York Heart Association class II–III) were included. All patients performed a symptom-limited exercise test with gas exchange analysis on a cycle ergometer. VAT was determined by the V-slope method and OUES was derived via least-squares linear regression using 100% (OUES100), 90% (OUES90), and 75% (OUES75) of exercise duration, and, in addition, by using only the first 50% of data points preceding VAT (OUES½VAT), all data preceding VAT (OUESVAT), and only data following VAT (OUESpostVAT). Whereas OUESVAT (1720 ± 430 ml/min/log(l/min)), OUES75 (1811 ± 476 ml/min/log(l/min)), and OUESpostVAT (1742 ± 564 ml/min/log(l/min)) were not significantly different from OUES100 (1767 ± 542 ml/min/log(l/min)), OUES½VAT (1500 ± 314 ml/min/log(l/min)) was significantly lower than all other values ( p < 0.01). When a VO2 plateau was present, OUES100 was lower than OUES90 ( p < 0.05). Conclusions: The study results indicate that OUES values should be interpreted with caution when CHF patients do not reach the ventilatory anaerobic threshold or when a VO2 plateau is present.